The Change in the Composition of Trichoderma reesei Carbohydrases Complex as a Result of Gamma Mutagenesis. (May 2019) - Kostyleva, Elena V; Sereda, Anna S; Osipov, Dmitrii O; Velikoretskaya, Irina A; Tsurikova, Nina V
The filamentous fungus Trichoderma reesei is traditionally used as the main industrial producer of cellulases and hemicellulases. Recently, the relevance of carbohydrases hydrolyzing nonstarch polysaccharides of cereals has significantly increased in feed production. In processing of grain raw materials, endodepolymerases, mainly xylanases and endoglucanases, play a key role. Earlier, we carried out gamma mutagenesis of an industrial strain T. reesei BCM18.2/KK to increase the proportion of endodepolymerases in its enzyme complex. Endoglucanase activity of the strain was increased 5-fold, while xylanase activity increased more than 8-fold. It was interesting to determine the carbohydrases composition in enzyme preparations obtained from the original and mutant T. reesei strains. So, the strains were cultured in laboratory fermenters; concentrated preparations were obtained using freeze dryer. It was established that gamma mutagenesis resulted in significant changes in the carbohydrases complex of the strain. Cellobiohydrolase I being the major carbohydrase in the original strain was absent in the enzyme complex of the mutant. The share of xylanases and endoglucanases in the preparation from the mutant strain increased by 6% and 6.5%, respectively, compared with the preparation from the original strain. The obtained data show the ability of gamma irradiation to affect the component composition of T. reesei carbohydrase complex.